Rhamnolipids and essential oils in the control of mosquito-borne tropical diseases - Salazar-Bryam, Ana Maria [UNESP]; Silva, Vinicius Luis [UNESP]; de Abreu, Marina Rodrigues [UNESP]; Matos, Renata Silva [UNESP]; da Rocha, Mateus Aparecido Gonçalves [UNESP]; Neves, Raphael Culim [UNESP]; Camargo-Mathias, Maria Izabel [UNESP]; Von Zuben, Claudio José [UNESP]; Lovaglio, Roberta Barros; Contiero, Jonas [UNESP] (Springer Nature, 2021)
The diseases transmitted by mosquito vectors are a great public health issue. Thus, effective vector control becomes the main strategy to reduce their prevalence. However, insecticide resistance has become a huge concern for the mitigation of mosquitoes; here, we propose the use of rhamnolipids in emulsion with clove oil against Aedes aegypti and Culex quinquefasciatus. The toxicity of rhamnolipids and clove oil to two species of mosquitoes transmitting tropical diseases was investigated. After 24 h, the LC50 was 140 mg/L when rhamnolipids were used and 154 mg/L when clove oil was used against Aedes aegypti larvae. In the case of Culex quinquefasciatus, the LC50 was 130 mg/L for rhamnolipids and 19 mg/L for clove oil. When the concentrations of the upper limits of one of the solutions (rhamnolipid or clove oil) were mixed, 100% mortality was obtained after 24 h. The bioassay of insecticidal action for solutions of rhamnolipids and clove oil in the lower limit, upper limit, and lethal concentration 50 to determine the effect on 50% of the population (KD50) achieved low results from KD50 to the upper limit compared to the other concentrations for both Aedes aegypti and Culex quinquefasciatus. The rhamnolipids and clove oil at the upper limit concentration had the greatest repellent activity against the two mosquito species. Bioassays using different concentrations of rhamnolipids revealed variations in the morphology of the intestinal epithelium (800 mg/L). A concentration of 900 mg/L led to the most severe morphological changes in the organization of the epithelium and the cells lining the intestines of these larvae. When larvae were exposed to a concentration of 1000 mg/L, the marginalization of chromatin in the nucleus of epithelial cells was very severe, indicating the onset of cell death. Key points • The toxicity of rhamnolipids and clove oil has a larvicidal, insecticidal, and repellent effect. • The combination of concentrations of these compounds enhances their action. • Different concentrations of rhamnolipids led to severe morphological changes in the organization of the epithelium and the cells and the intestines of larvae. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Aedes aegypti; Clove oil; Culex quinquefasciatus; Pseudomonas aeruginosa; Rhamnolipids